Effects of head flexion posture on the multidirectional static force capacity of the neck. (August 2016) - Gilchrist, Ian; Moglo, Kodjo; Storr, Michael; Pelland, Lucie
Abstract: Background: Neck muscle force protects vertebral alignment and resists potentially injurious loading of osteoligamentous structures during head impacts. As the majority of neck muscles generate moments about all three planes of motion, it is not clear how the force capacity of the neck might be modulated by direction of force application and head posture. The aim of our study was to measure the multidirectional moment-generating capacity of the neck and to evaluate effects of 20° of head flexion, a common head position in contact sports, on the measured capacity. Methods: We conducted a cross-sectional study, with 25 males, 20–30 years old, performing maximum voluntary contractions, with ballistic intent, along eight directions, set at 45° intervals in the horizontal plane of the head. Three-dimensional moments at C3 and T1 were calculated using equations of static equilibrium. The variable of interest was the impulse of force generated from 0–50 ms. Effects of direction of force application and head posture, neutral and 20° flexion, were evaluated by two-way analysis of variance and linear regression. Findings: Impulse of force was lower along diagonal planes, at 45° from the mid-sagittal plane, compared to orthogonal planes ( P  < 0.001). Compared to neutral posture, head flexion produced a 55.2% decrease in impulse capacity at C3 and 45.9% at T1 . Interpretation: The risk of injury with head impact would intrinsically be higher along diagonal planes and with a 20° head down position due to a lower moment generating capacity of the neck in the first 50 ms of force application. Highlights: The static impulse capacity of the neck provides restraint against potentially injurious forces. Head flexion produces a significant decreased in impulse capacity. Effects are most notable along diagonal planes, which include a large component of axial rotation. Standardized quantification of impulse capacity could discriminate athletes at risk for neck injuries.